2021
DOI: 10.1111/are.15528
|View full text |Cite
|
Sign up to set email alerts
|

Enrofloxacin induces intestinal disorders of metabolome and microbiome in American shad ( Alosa sapidissima )

Abstract: side effects and rapid action compared with other antibiotics (Liu et al., 2015;Wang et al., 2016). With societal development, residual antibiotics flow into aquatic environments through wastewater systems from hospitals, pharmaceutical industries, livestock and aquaculture (Fiaz et al., 2021). ENR has been detected in water, sediment, soil and animal tissue worldwide and ultimately enters the human body through the food chain (Huang et al., 2020). Growing evidence showed that ENR affected human health by eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Recent studies suggest the general immunotoxicity of ENR in different fish species. For example, dysfunction of the immune system was shown in American shad (Alosa sapidissima) after a dietary exposure of 100 mg/kg ENR for 30 days . Our previous study found that ENR targeted primary fish macrophages and reduced the phagocytic function of macrophages that were mediated but not limited to the NF-kB pathway .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest the general immunotoxicity of ENR in different fish species. For example, dysfunction of the immune system was shown in American shad (Alosa sapidissima) after a dietary exposure of 100 mg/kg ENR for 30 days . Our previous study found that ENR targeted primary fish macrophages and reduced the phagocytic function of macrophages that were mediated but not limited to the NF-kB pathway .…”
Section: Introductionmentioning
confidence: 99%
“…For example, dysfunction of the immune system was shown in American shad (Alosa sapidissima) after a dietary exposure of 100 mg/kg ENR for 30 days. 13 Our previous study found that ENR targeted primary fish macrophages and reduced the phagocytic function of macrophages that were mediated but not limited to the NF-kB pathway. 6 Other potential pathways and detailed mechanisms of ENR immunotoxicity are still largely unknown, particularly at the early life stage of high sensitivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The shad were introduced to China in 2003 and successfully cultured in freshwater indoor systems for nearly 20 years in China [ 15 ]. The shad has become one of the most expensive farmed species in China, which has prompted an upsurge in consumption [ 16 ]. However, shad has quite distinctive dimorphism in body size and behaviors between sexes.…”
Section: Introductionmentioning
confidence: 99%